2003
DOI: 10.1103/physrevlett.90.127402
|View full text |Cite
|
Sign up to set email alerts
|

Electrophosphorescence and Delayed Electroluminescence from Pristine Polyfluorene Thin-Film Devices at Low Temperature

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 26 publications
3
46
1
Order By: Relevance
“…Further, King et al have also shown unambiguously that DF accounts for up to 25% of the total EL output in other polymer devices17 from measurements of delayed electroluminescence, first observed by Sinha et al10 Secondary singlet states generated by TF thus give rise to total singlet yields which exceed the classical spin statistical limit of 0.25 in both polymer and small molecule OLED devices, implying that charge recombination does not have to violate spin statistics in order to exceed an internal quantum efficiency of 25% 18. In order to understand the total secondary singlet production mechanism we set out to measure directly the efficiency that singlets are produced from triplets in PSBF.…”
Section: Introductionmentioning
confidence: 81%
“…Further, King et al have also shown unambiguously that DF accounts for up to 25% of the total EL output in other polymer devices17 from measurements of delayed electroluminescence, first observed by Sinha et al10 Secondary singlet states generated by TF thus give rise to total singlet yields which exceed the classical spin statistical limit of 0.25 in both polymer and small molecule OLED devices, implying that charge recombination does not have to violate spin statistics in order to exceed an internal quantum efficiency of 25% 18. In order to understand the total secondary singlet production mechanism we set out to measure directly the efficiency that singlets are produced from triplets in PSBF.…”
Section: Introductionmentioning
confidence: 81%
“…Generally, slow transient emissions in OLEDs are ascribed to either the recombination of charges from deep traps or interfacial charge layers or TTA. 10,24,25 In order to distinguish between the two mechanisms, the same transient electroluminescence trace has been measured with the application of a 10 V for 200 ns long reverse bias pulse 100 ns after the turn off of the device current. This pulse will remove, or at least perturb significantly, any trapped charge contribution to the decay of the luminance.…”
Section: Resultsmentioning
confidence: 99%
“…The nature of excited state species and interactions that optically detected magnetic resonance (ODMR) and photoluminescence detected magnetic resonance (PLDMR) actually detect is not clear. For example, Segal et al [82,83] have proposed the importance of PL quenching arising from singlet (and triplet) exciton polaron interactions in these polymers, a process that we have shown to be efficient in working PLED devices [84,85]. Further studies have tried to determine the relative singlet to triplet yield by employing emissive (phosphorescent) acceptors [60,86].…”
Section: Experimental Observationsmentioning
confidence: 99%
“…This also shows that for singlet excitons, quenching by the electric field [99] or by polarons [100] is negligible under the conditions used in our experiments. For the triplet signal, either triplet transient absorption [90,101] or phosphorescence [85] could be used. However, both require large excitation densities to yield appropriate signal-to-noise ratios, which also causes migration activated TTA a major quenching channel [102,103].…”
Section: Experimental Observationsmentioning
confidence: 99%